Optimalisasi Penugasan Karyawan Jasa Ekspedisi Menggunakan Metode Hungarian (Studi Kasus CV. Anteraja Cabang Mekarmukti) - Lutfi Nur Rahman; Wahyudin Wahyudin (Fakultas Teknik, 2021)
The Covid-19 pandemic has prompted an increase in e-commerce orders as people prefer to buy their needs online. This impact occurs in the development of the freight forwarding service industry that takes a long time to deliver goods to consumers so that delivery is not optimal in one day. CV. Anteraja Mekarmukti branch is one of the shipping service provider expedition companies that has 14 couriers in charge of delivering packages to 14 delivery points in Cikarang Baru. The problem that is often experienced by CV. Anteraja Mekarmukti branch is related to the allocation of couriers that result in long delivery time. The method used in this study was the Hungarian Method to minimize time by placing courier delivery at the destination. Based on the results of the study, after using the Hungarian Method obtained the delivery time of goods on the CV. Anteraja is 172 minutes, where there is a reduction in the delivery time of goods by 30 minutes and time efficiency by 14.85% when compared to the completion time before using the Hungarian method of 202 minutes.